On Amnesia and Knowing-How. - Bzdak, David (Techné: Research in Philosophy & Technology)
In this paper, I argue that Stanley and Williamson's 2001 account of knowledge-how as a species of knowledge-that is wrong. They argue that a claim such as "Hannah knows how to ride a bicycle" is true if and only if Hannah has some relevant knowledge-that. I challenge their claim by considering the case of a famous amnesic patient named Henry M. who is capable of acquiring and retaining new knowledge-how but who is incapable of acquiring and retaining new knowledge-that. In the first two sections of the paper, I introduce the topic of knowledge-how and give a brief overview of Stanley and Williamson's position. In the third and fourth sections, I discuss the case of Henry M. and explain why it is plausible to describe him as someone who can retain new knowledge-how but not new knowledge-that. In the final sections of the paper, I argue that Henry M.'s case does indeed provide a counterexample to Stanley and Williamson's analysis of knowing-how as a species of knowing-that, and I consider and respond to possible objections to my argument.